Imaging continental breakup using teleseismic body waves: The Woodlark Rift, Papua New Guinea. (7th August 2015) - Eilon, Zachary; Abers, Geoffrey A; Gaherty, James B; Jin, Ge
Abstract: This study images the upper mantle beneath the D'Entrecasteax Islands, Papua New Guinea, providing insight into mantle deformation beneath a highly rifted continent adjacent to propagating spreading centers. Differential travel times from P and S ‐wave teleseisms recorded during the 2010–2011 CDPapua passive seismic experiment are used to invert for separate VP and VS velocity models of the continental rift. A low‐velocity structure marks the E‐W axis of the rift, correlating with the thinnest crust, high heat flow, and a linear trend of volcanoes. This slow region extends 250 km along strike from the oceanic spreading centers, demonstrating significant mantle extension ahead of seafloor breakup. The rift remains narrow to depth indicating localization of extension, perhaps as a result of mantle hydration. A high‐ VP structure at depths of 90–120 km beneath the north of the array is more than 6.5% faster than the rift axis and contains well‐located intermediate depth earthquakes. These independent observations place firm constraints on the lateral thermal contrast at depth between the rift axis and cold lithosphere to the north that may be related to recent subduction, although the polarity of subduction cannot be resolved. This geometry is gravitationally unstable; downwelling or small‐scale convection could have facilitated rifting and rapid lithospheric removal, although this may require a wet mantle to be realistic on the required time scales. The high‐ V structure agrees with the maximum P, T conditions recorded by young ultra‐high pressure rocks exposed on the rift axis and may be implicated in their genesis. Key Points: Body wave inversion for mantle structure within highly extended continental rift Slow, narrow rift axis demonstrates mantle extension ahead of seafloor breakup Well‐constrained thermal contrast between rift and fast seismogenic structure